Design and experiment of a flexible end effector for seedling picking with adjustable clamping diameter - Ren, Zhaoyang; Hu, Minjuan; Li, Kun; Yan, Wei; Ji, Yao; Yang, Youfu; Yuan, Peichao; Zhang, Wenyi (International Journal of Agricultural and Biological Engineering, 2026)
To improve the adaptability of the stem-clamping end effector to variations in pepper plug seedling stem diameter, a flexible seedling-picking end effector with an adjustable gripping diameter was developed. The closing clearance between the two gripper plates was preset by replacing the miniature cam-follower bearing with bearings of different outer diameters, while rubber-covered gripping surfaces provided passive compliance and reduced the risk of stem damage and slippage. Based on the geometric relationship among the claw, connecting rod, push rod, and cam, the maximum claw opening and push-rod stroke were determined to be 32 and 4.7 mm, respectively, and the cam profile was designed to coordinate the opening, closing, holding, and releasing actions of the gripper. Mechanical tests showed that the average maximum pull-out resistance at picking angles of 0°, 20°, and 40° were 1.20, 1.18, and 1.29 N, respectively, which were substantially lower than the maximum tensile load of the seedling stems. Compared with rigid aluminum gripping surfaces, the rubber-covered gripper plates reduced the stem breakage rate from 66.67%-80.00% to 3.33%-6.67% and increased the transfer success rate from 76.67%-86.67% to 83.33%-93.33%. A three-factor Box-Behnken experiment was conducted using the rotational speed of the seedling-picking mechanism, stem diameter, and miniature-bearing outer diameter as experimental factors. Response surface optimization identified an optimal parameter combination of 66.1785 r/min for the rotational speed of the seedling pick-up mechanism, 2.1991 mm for the seedling stem diameter, and 10.0811 mm for the micro-bearing outer diameter. Under these conditions, the predicted seedling pick-up success rate and seedling injury rate were 93.1296% and 2.2087%, respectively, with an overall desirability of 0.976. The results demonstrate that the proposed end effector can preset the gripping diameter and reduce stem damage and slippage risks under the tested conditions, providing a practical design for automatic seedling picking. Key words: adjustable clamping diameter; end effector for seedling picking; seedling picking mechanism; stem clamping; non-circular gear; automated transplanting; experimental design DOI: 10.25165/j.ijabe.20261904.10235 Citation: Ren Z Y, Hu M J, Li K, Yan W, Ji Y, Yang Y F, et al. Design and experiment of a flexible end effector for seedlingpicking with adjustable clamping diameter. Int J Agric & Biol Eng, 2026; 19(4): 123–132.